Discontinuation of hypnotics during cognitive behavioural therapy for insomnia - Závěšická, Lucie; Brunovský, Martin; Matoušek, Miloš; Šóš, Peter (BMC psychiatry, 2008)
BACKGROUND: In practical sleep medicine, therapists face the question of whether or not to discontinue the ongoing use of hypnotics in patients, as well as the possible effects of discontinuation. The aim of this study was to evaluate the effects of discontinuing third-generation hypnotics on the results of cognitive-behavioural therapy (CBT) for primary insomnia in patients after long-term abuse. METHODS: Twenty-eight outpatients were treated by CBT for 8 weeks. The treatment outcome was estimated by means of differences among subjective clinical scales and polysomnography variables assessed before and after the treatment period. The therapeutic effect in a subgroup of 15 patients who had previously received hypnotics and were successively withdrawn during weeks 2-6 was compared to the effect achieved in patients who had not used hypnotics before CBT. RESULTS: There were no significant differences in baseline subjective and objective sleep characteristics between the hypnotic abusers and non-abusers. According to clinical scales and most polysomnographic measures, CBT was highly effective in both groups of subjects; it produced the greatest changes in total sleep time, REM sleep and sleep efficiency. Unexpectedly, discontinuation of hypnotics, as a factor in the analysis, was followed by an additional improvement of sleep efficiency and wake after sleep onset parameters. CONCLUSION: Our study confirmed the efficacy of CBT in both hypnotic-abusing and non-abusing patients with chronic insomnia. The results of this study suggest that tapered withdrawal of third-generation hypnotics during CBT therapy for chronic insomnia could be associated with improvement rather than worsening of sleep continuity.
Keywords: Sleep, REM; Male; Withholding Treatment; nenasazení léčby; Polysomnography; Sleep Initiation and Maintenance Disorders; Adult; Aged; dospělí; mužské pohlaví; senioři; polysomnografie; Drug Therapy; spánek REM; Cognitive Behavioral Therapy; kognitivně behaviorální terapie; poruchy iniciace a udržování spánku; farmakoterapie; lidé; ženské pohlaví; Humans; hypnotika a sedativa; Female; lidé středního věku; Hypnotics and Sedatives; Middle Aged